An Experimental Investigation on Low Load Combustion Stability and Cold-Firing Capacity of a Gasoline Compression Ignition Engine. (June 2019) - Zhou, Lei; Hua, Jianxiong; Wei, Haiqiao; Han, Yiyong
Highlights: Idling combustion stabilities with various injection strategies are studied. Stable idling has been achieved under zoom temperature and atmospheric pressure. An effective method to achieve the firing of a cold GCI engine has been proposed. Abstract: Gasoline compression ignition (GCI) is one of the most promising combustion concepts to maintain low pollutant emissions and high efficiency. However, low load combustion stability and firing in cold-start operations are two major challenges for GCI combustion. Strategies including negative valve overlap (NVO), advanced injection strategies, fuel reforming, and intake preheating have been proposed in order to solve these difficulties; however, the cold start is still an obstacle. The objective of this work is to study effective methods to achieve GCI engine cold start-up. This work combines NVO, in-cylinder fuel reforming, and intake preheating to achieve quick firing under cold-start conditions and the subsequent warm-up conditions. The results show that start of injection (SOI) during the intake stroke yields the best fuel economy, and injection during the compression stroke has the potential to extend the low load limit. Furthermore, SOI during the NVO period grants the ability to operate under engine conditions with cold intake air and coolant. With highly reactive products made by in-cylinder fuel reforming and fast heat accumulation in the combustion chamber, the NVO injection strategy is highly appropriate for GCI firing. An additional assisted technical method, such as intake preheating, is required to ignite the first firing cycle for a cold-start process. With the combination of NVO, in-cylinder fuel reforming, and intake preheating, the GCI engine successfully started within five combustion cycles in the experiment. After the firing process, the engine could stably operate without further intake preheating; thus, this method is appropriate for engine cold-start and warm-up.